2014
DOI: 10.1103/physrevd.89.084011
|View full text |Cite
|
Sign up to set email alerts
|

Complementarity plus backreaction is enough

Abstract: We investigate a recent development of the black hole information problem, in which a practical paradox has been formulated to show that complementarity is insufficient. A crucial ingredient in this practical paradox is to distill information from the early Hawking radiation within the past light cone of the black hole. By causality this action can backreact on the black hole. Taking this backreaction into account, the paradox could be resolved without invoking any new physics beyond complementarity. This reso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…If so, then it may be that some version of black hole complementarity as described in section 5.7 may yet provide an escape from the apparent inconsistency of unitary evaporation and smooth infall without requiring an observable breakdown of some principle of physics. Several reasons why the AMPS experiment might be impossible have been proposed [154][155][156][157], but in my view the most robust is my own observation with Patrick Hayden that the computational complexity of "distilling" the purification R B from the Hawking radiation is so severe that it almost certainly requires an exponential amount of time in the entropy of the black hole [49]. This far exceeds the evaporation time, which is only of order S 3/2 in Planck units, so the infalling observer of figure 26 will not succeed in extracting R B until long after the black hole has evaporated and she can no longer jump in and see a contradiction.…”
Section: Complementarity From Computational Complexity?mentioning
confidence: 99%
“…If so, then it may be that some version of black hole complementarity as described in section 5.7 may yet provide an escape from the apparent inconsistency of unitary evaporation and smooth infall without requiring an observable breakdown of some principle of physics. Several reasons why the AMPS experiment might be impossible have been proposed [154][155][156][157], but in my view the most robust is my own observation with Patrick Hayden that the computational complexity of "distilling" the purification R B from the Hawking radiation is so severe that it almost certainly requires an exponential amount of time in the entropy of the black hole [49]. This far exceeds the evaporation time, which is only of order S 3/2 in Planck units, so the infalling observer of figure 26 will not succeed in extracting R B until long after the black hole has evaporated and she can no longer jump in and see a contradiction.…”
Section: Complementarity From Computational Complexity?mentioning
confidence: 99%
“…Another argument posits that the firewall paradox is likely to be an artifact of using an effective theory beyond its domain of validity [137]. It has been suggested that a distillation-like process for extracting information needs to be clarified before one can conclude that black hole complementarity is not valid [138]; indeed this distillation process may back-react on the black hole, breaking cross-horizon entanglement and removing the firewall [139].…”
Section: Loopholesmentioning
confidence: 99%
“…Several scholars have argued that the only resolution to the information paradox problem associated with black holes is by the creation of new physics [29]. In a recent paper, Hui and Yang [30] show that by taking back-reaction into account, the paradox can be resolved without invoking any new physics beyond complementarity. We agree with this conclusion that no new physics is required, only the conjecture that the two principles are fundamentally tied together.…”
Section: Figure 1 Linking Veiled Nonlocality and Cosmic Censorshipmentioning
confidence: 99%